2022
DOI: 10.3390/d14090745
|View full text |Cite
|
Sign up to set email alerts
|

Different Chromosome Segregation Patterns Coexist in the Tetraploid Adriatic Sturgeon Acipenser naccarii

Abstract: The Adriatic sturgeon, Acipenser naccarii (Bonaparte, 1836), is a critically endangered tetraploid endemism of the Adriatic region; it has been targeted, over the last 20 years, by different conservation programs based on controlled reproduction of captive breeders followed by the release of their juvenile offspring; its preservation would greatly benefit from the correct and coordinated management of the residual genetic variability available in the different captive stocks. In this sense, the setup of an eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This can be explained by the presence of duplicate regions or as a trace of an ancestral genomic duplication [21]. Recently, it was also observed that in A. naccarii, some loci follow a disomic segregation modality [22], indicative of a further differentiation of the chromosomes towards a diploid condition [23]. In summary, the coexistence of different ploidy levels in different regions of the genome makes the development of analytical methods for sturgeon species belonging to the group with 240 chromosomes challenging [21].…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the presence of duplicate regions or as a trace of an ancestral genomic duplication [21]. Recently, it was also observed that in A. naccarii, some loci follow a disomic segregation modality [22], indicative of a further differentiation of the chromosomes towards a diploid condition [23]. In summary, the coexistence of different ploidy levels in different regions of the genome makes the development of analytical methods for sturgeon species belonging to the group with 240 chromosomes challenging [21].…”
Section: Discussionmentioning
confidence: 99%